In vitro-ex vivo correlations between a cell-laden hydrogel and mucosal tissue for screening composite delivery systems - Anna K. Blakney; Adam B. Little; Yonghou Jiang; Kim A. Woodrow (Taylor & Francis Group, 2017)
Composite delivery systems where drugs are electrospun in different layers and vary the drug stacking-order are posited to affect bioavailability. We evaluated how the formulation characteristics of both burst- and sustained-release electrospun fibers containing three physicochemically diverse drugs: dapivirine (DPV), maraviroc (MVC) and tenofovir (TFV) affect in vitro and ex vivo release. We developed a poly(hydroxyethyl methacrylate) (pHEMA) hydrogel release platform for the rapid, inexpensive in vitro evaluation of burst- and sustained-release topical or dermal drug delivery systems with varying microarchitecture. We investigated properties of the hydrogel that could recapitulate ex vivo release into nonhuman primate vaginal tissue. Using a dimethyl sulfoxide extraction protocol and high-performance liquid chromatography analysis, we achieved >93% recovery from the hydrogels and >88% recovery from tissue explants for all three drugs. We found that DPV loading, but not stacking order (layers of fiber containing a single drug) or microarchitecture (layers with isolated drug compared to all drugs in the same layer) impacted the burst release in vitro and ex vivo. Our burst-release formulations showed a correlation for DPV accumulation between the hydrogel and tissue (R2= 0.80), but the correlation was not significant for MVC or TFV. For the sustained-release formulations, the PLGA/PCL content did not affect TFV release in vitro or ex vivo. Incorporation of cells into the hydrogel matrix improved the correlation between hydrogel and tissue explant release for TFV. We expect that this hydrogel-tissue mimic may be a promising preclinical model to evaluate topical or transdermal drug delivery systems with complex microarchitectures.